2021
DOI: 10.1115/1.4050131
|View full text |Cite
|
Sign up to set email alerts
|

Code Verification of Non-Newtonian Fluid Solvers for Single- and Two-Phase Laminar Flows

Abstract: The presence of complex fluids in nature and industrial applications combined with the rapid growth of computer power over the past decades has led to an increasing number of numerical studies on non-Newtonian flows. In most cases, non-Newtonian models can be implemented in existing Newtonian solvers by relatively simple modification of the viscosity. However, due to scarcity of analytical solutions for non-Newtonian fluid flows and widespread use of regularisation methods, performing Code Verification to ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Combining the evidence of our previous code verification exercises [30,31] and the results of this work, it is concluded that the power-law, Bingham and Herschel-Bulkley models are implemented correctly and that the code is capable of reproducing literature data with good accuracy despite the high non-linearity introduced by the non-Newtonian viscosity. This provides confidence to employ REFRESCO for more complex applications such as a ship sailing through fluid mud.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Combining the evidence of our previous code verification exercises [30,31] and the results of this work, it is concluded that the power-law, Bingham and Herschel-Bulkley models are implemented correctly and that the code is capable of reproducing literature data with good accuracy despite the high non-linearity introduced by the non-Newtonian viscosity. This provides confidence to employ REFRESCO for more complex applications such as a ship sailing through fluid mud.…”
Section: Discussionsupporting
confidence: 72%
“…The two schemes have the same computational cost, thus, in principle, there is no reason to prefer one scheme to the other. Furthermore, when we performed a code verification exercise (not shown here) similar to that in [30], the two schemes exhibited the same accuracy and rate of convergence of the residuals. However, on the present problem, the first scheme (Eq.…”
Section: Iterative Convergence and Viscosity Interpolation Schemementioning
confidence: 88%
See 1 more Smart Citation
“…By eliminating the presence of the basis functions in (31) and (32), we have eliminated the solutiondiscretization error.…”
Section: Solution-discretization Error Eliminationmentioning
confidence: 99%
“…Code verification has been performed on computational physics codes associated with several physics disciplines, including aerodynamics [20], fluid dynamics [21][22][23][24][25][26][27], solid mechanics [28], fluid-structure interaction [29], heat transfer in fluid-solid interaction [30], multiphase flows [31,32], radiation hydrodynamics [33], electrostatics [34], electrodynamics [35], and ablation [36][37][38][39][40]. For surface integral equations in computational electromagnetics, code-verification activities that employ manufactured solutions have been limited to the EFIE [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%